PENERAPAN PROGRAM TYPING MASTER DALAM MENINGKATKAN KECEPATAN DAN KETELITIAN PENGETIKAN 10 JARI BUTA - Mariskha. Z Mariskha. Z; Esya Alhadi; Titi Andriyani (Politeknik Negeri Sriwijaya, 2016)
State Polytechnic of Sriwijaya Palembang is a vocational education Institution which in the lecture activities more practical rather than theoretical, as well as within the Department of Business Administration. Department of Business Administration is a subject that study a lot in the areas of secretarial and office including the practice of typing. During this time students at the Business Administration Department trained 10 finger blind typing skills by using a manual typewriter and electronic typewriter. In accordance with current technological developments every company is already using technology such as computers. Therefore, students should be able to follow the development of the technology that is the way to learn to type fast 10-finger blind which should still pay attention to precision and accuracy. There are several kinds of programs that can be used for learning in typing speed, one of which is a master typing program. Typing master's program is often used in polytechnic typing speed competition in Indonesia, unfortunately; only few business administration departments used this master typing program recently. Therefore, with this program it can be known the strengths and weaknesses of this typing master program.